Enhancing the legal framework to promote green capital flows in Vietnam’s financial market - Le Hoang Lan (Journal of State Management, 2024)
Unfolding green capital flows for the business sector has been a primary concern for both the business community and state management in the financial and banking sectors. Green capital flows are vital in funding to achieve sustainable development and green growth goals, particularly in addressing environmental and climate-related challenges. In recent years, green capital flows have been implemented through green bonds and credits, yielding promising outcomes in energy saving, renewable energy, clean agriculture, and high-tech agriculture. However, their current state reveal numerous obstacles and challenges, necessitating policy adjustments, legal amendments, and the regulatory framework's improvement to ensure the Net-Zero target's achievement by 2050.